A Nurse-Led Care Program for Breast Cancer Patients in a Chemotherapy Day Center: A Randomized Controlled Trial. Issue 1 (January 2019) - Lai, Xiao Bin; Ching, Shirley Siu Yin; Wong, Frances Kam Yuet; Leung, Carenx Wai Yee; Lee, Lai Ha; Wong, Jessica Shuk Yin; Lo, Yim Fan
Abstract : Background: Healthcare providers are facing the challenge of helping cancer patients cope with the impact of outpatient-based chemotherapy. A nurse-led care program was proposed to address this challenge. Objective: The aim of this study was to examine the effects of a nurse-led care program for patients receiving outpatient-based chemotherapy. Methods: This was a single-center, open-label, 2-arm parallel trial with equal randomization (NCT02228200). Breast cancer patients in Hong Kong were randomly allocated to the intervention arm or the control arm. The control arm received routine hospital care. The intervention arm received the nurse-led care plus the routine hospital care. The quality of life, self-efficacy, symptom distress levels, and satisfaction with care were evaluated with questionnaires before randomization (T0), in the middle of chemotherapy (T1), and 1 month after chemotherapy (T2). Individual interviews were conducted with some participants in the intervention arm at T2. Results: The intervention arm participants reported significantly lower distress levels from oral problems, fatigue, peripheral neuropathy, distressful feelings, and higher satisfaction with care. According to the satisfaction evaluation and the interviews, the participants stated that the service was helpful in providing information and communication opportunities, filling the service gap after drug administration, providing psychological support, relieving discomfort, and building confidence. Conclusion: Breast cancer patients received support from the provision of comprehensive, continuous, and individualized care. Implications for Practice: The nurse-led care program could be applied to breast cancer patients in other hospitals in Hong Kong. Exploring its applicability to cancer settings in other countries is recommended.